2017
DOI: 10.3390/fermentation3020027
|View full text |Cite
|
Sign up to set email alerts
|

Reappraising a Controversy: Formation and Role of the Azodication (ABTS2+) in the Laccase-ABTS Catalyzed Breakdown of Lignin

Abstract: Abstract:In fermentations of lignocelluloses, redox potentials (If not indicated otherwise, redox potentials in Volt are taken versus Normal Hydrogen Reference Electrodes (NHE).) E 0 of laccases/plant peroxidases by 0.79/0.95 V enable oxidations of phenolic substrates and transformations of synthetic and substrate-derived compounds to radicals that mediate attacks on non-phenolic lignin (models) by 1.5 V. In consecutive one-electron abstractions, the redox mediator 2,2 -azinobis-(3-ethylbenzothiazoline-6-sulfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 65 publications
0
19
0
1
Order By: Relevance
“…The ABTS •+ radical cation can undergo further oxidation to form the dication ABTS 2+ with λ max at 513-520 nm, ε 36 000 L mol −1 cm −1 (see Figure 2a) [42]). The ABTS 2+ formation kinetics from ABTS •+ , when an excess of S 2 O 8 2− is applied, is approximately three times slower than the radical cation ABTS •+ formation from ABTS [47,48]. Apparently, the ABTS 2+ dication does not influence ABTS/PP assay measurements as it has rather low solubility in water and is relatively stable only in the excess of S 2 O 8 2− anions or in a very acidic medium, with any aqueous dilution resulting in a shift of the reaction balance back to ABTS •+ [41,[47][48][49][50][51].…”
Section: Abts/pp Basic Chemistrymentioning
confidence: 96%
“…The ABTS •+ radical cation can undergo further oxidation to form the dication ABTS 2+ with λ max at 513-520 nm, ε 36 000 L mol −1 cm −1 (see Figure 2a) [42]). The ABTS 2+ formation kinetics from ABTS •+ , when an excess of S 2 O 8 2− is applied, is approximately three times slower than the radical cation ABTS •+ formation from ABTS [47,48]. Apparently, the ABTS 2+ dication does not influence ABTS/PP assay measurements as it has rather low solubility in water and is relatively stable only in the excess of S 2 O 8 2− anions or in a very acidic medium, with any aqueous dilution resulting in a shift of the reaction balance back to ABTS •+ [41,[47][48][49][50][51].…”
Section: Abts/pp Basic Chemistrymentioning
confidence: 96%
“…Comparable disintegrations of the red ABTS 2+ related product were also documented in preliminary Fourier-transform infrared spectrometry (FT-IR) analyses [62]. The lilac precipitates of a completely by K 2 O 8 S 2 oxidized monoazo compound of functional ABTS showed major stretching vibrations at 1506.6, 1472.8, and 1441.4 cm −1 .…”
Section: Liquid Chromatography-mass Spectrometry (Lc-ms) Examination mentioning
confidence: 94%
“…Contemplating the treatments 1a and 4b with Cu(II) as the only efficient Fenton metal (Table 1), it is concluded that plants initiate oxidative activities in the rhizosphere by the release of peroxidases, carboxylates, and occasional traces of active oxygen species at least in alfalfa [38]. Azodication derivatives in the culture fluids confirm the presence of root-released phenolic molecules, too, that had been oxidized to aryloxy radicals with the respective redox mediator potential [62]. Their formation could mainly be ascribed to the PO/active-oxygen couple but also to the by-production of Mn 3+ with the aid of the radicals in turn.…”
Section: Interaction Of Catalystsmentioning
confidence: 98%
See 2 more Smart Citations